O corpo e o outro: constituição da alteridade em uma perspectiva bakhtiniana de O Silmarillion de J. R. R. Tolkien em cotejo com o racismo - Rufo, Alline Duarte (Universidade Federal de São Carlos, 2020)
This thesis proposes to understand how determined bodies are valued as negative in the work The Silmarillion, from J. R. R. Tolkien, especially because there is a marked division of different peoples and bodies in it, as well as an ethical and aesthetical relation, in which the author created one of the most complex and vast fictional universes for developing languages, ages, peoples, maps, and cosmogony. The theoretical-methodological basis of this work is based on the studies developed by the Russian philosopher of language Mikhail Bakhtin and the other thinkers of the Circle, mainly on the concepts of alterity, body, and grotesque realism. Thus, starting from a historical materialist methodology, the body, as a social construct, is part of an I-other relationship, being valued. Those who somehow transgress the current rules of a world are called monsters, building an aesthetical and ethical withdrawal from the human that acts as a process of social exclusion and extermination. Concomitantly, in the ethical world, one can observe how these mechanisms of social exclusion and death are part of the racism towards the black population. That said, to a comprehension of that valuation in art and in life, this work compared news about racism in Brazil. Thus, it is concluded that when one observes these bodies from a bakhtinian perspective, he understands that they are grotesque bodies, once they are a transgression and all those who are oppressed, negatively valued, excluded and killed, they are so from their bodies and their experience for breaking a current rule. Therefore, existing is a profoundly revolutionary act, for it is to resist.
The body and the other: constitution of alterity in a Bakhtinian perspective of The Silmarillion by J. R. R. Tolkien in comparison with racism
Keywords: Mikhail Bakhtin; J. R. R. Tolkien; Corpo; Monstro; Grotesco; Racismo; Body; Monster; Grotesque; Racism; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES